2016
DOI: 10.3109/14767058.2016.1151869
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery complications in women with morbid obesity

Abstract: Wound complications, particularly separations, increase with BMI ≥ 50 compared to a lesser degree of morbid obesity. Skin closure techniques and self-retaining retractor use were not associated with cesarean wound complications in patients with morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…A total of 13 studies 14e26 that described 3,722,477 pregnancies (range, 112e2,176,673) were included in the metaanalysis. Of these, 8 studies 14,16,18e21,23,25 were included in the primary analysis, and 5 studies 15,17,22,24,26 were included in the subgroup analysis. BMI categories that were considered in the included studies are given in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies 14e26 that described 3,722,477 pregnancies (range, 112e2,176,673) were included in the metaanalysis. Of these, 8 studies 14,16,18e21,23,25 were included in the primary analysis, and 5 studies 15,17,22,24,26 were included in the subgroup analysis. BMI categories that were considered in the included studies are given in Supplementary Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 18,20 of the 8 studies that were included in the primary analysis presented data on underweight women, although all presented data on outcomes that were stratified by standard BMI, overweight, and the 3 classes of obesity. Of those that were included in subgroup analysis, 4 studies 17,22,24,26 enabled comparisons to be made between women with a BMI of 40e49.9 kg/ m 2 and those with a BMI of 50 kg/m 2 , and 2 studies 15,17 enabled comparisons to be made between women with a BMI of 50e59.9 kg/m 2 and a BMI of 60 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In probably the largest sample reported (38,229 women), wound complications occurred in 14% of women with BMI ≥ 45 kg/m 2 following cesarean delivery [25]. Wound separations in particular are seen more frequently in patients with super obesity [30].…”
Section: Wound Complicationsmentioning
confidence: 99%
“…Self-retaining retractors, unfortunately, have also not been found to reduce surgical site infection [30,82].…”
Section: Prevention Of Surgical Site Infectionsmentioning
confidence: 99%
“…6 Specifically, Vermillion et al 7 have shown that when the thickness of the subcutaneous tissue is > 3 cm the relative risk of developing wound infection reaches 2.8. Recently, Yamasato et al 8 . suggested that the rates of wound dehiscence tend to increase as the body mass index (BMI) increases.…”
Section: Introductionmentioning
confidence: 99%